POTENSI PENINGGALAN ARKEOLOGI KANTOR POS GORONTALO SEBAGAI DAYA TARIK WISATA SEJARAH - Arrazaq, Naufal Raffi; Tasnur, Irvan (UHN IGB Sugriwa Denpasar, 2025)
This study aims to analyze the potential of the Gorontalo Post Office archaeological heritage as a historical tourism attraction. The research employs a qualitative method. The findings indicate that the Gorontalo Post Office holds significant historical value, making it a relevant educational resource for tourists. The site has the potential to become an appealing historical tourism destination through preservation-based management. An adaptive conservation approach, which maintains the authenticity of the building while introducing new functions, such as a mini museum, is considered effective in enhancing its appeal. The involvement of local communities in management and promotion is also a crucial factor in supporting the sustainability of historical tourism. Utilizing digital technology, such as social media and augmented reality-based applications, can expand promotional reach and attract younger generations. This study concludes that the archaeological heritage of the Gorontalo Post Office possesses potential as a historical tourism attraction in terms of historical, cultural, and economic aspects. With integrated management and collaboration among the government, academics, and the private sector, the Gorontalo Post Office can become a historical tourism icon that not only strengthens Gorontalo's cultural identity but also contributes to local economic development and the preservation of cultural heritage for future generations.Top of Form